Hybrid-Key Agreement Protocol based on Chebyshev Polynomials - Ta, Thi Kim Hue; Nguyen, Minh Duc; Vu, Minh Hoang; Cuong, Hoang Manh (Old Journal, 2019)
This paper presented implementation of the Chebyshev permutation polynomials on hardware. The experimental results demonstrate that this is an efficient way to calculate the Chebyshev polynomials in a prime field. According to the hardware structure of the Chebyshev polynomial, a Hybrid-Key Agreement Protocol is proposed. The purpose of our protocol is to enable two end-users exchanging a secret session key using both the key distribution center and the Chebyshev-based public key encryption. Advantage of public-key encryption is authentic and confidential for delivering secret keys, the addition of KDCs serves a widely distributed set of users. The proposed key agreement protocol offers satisfactory security and can be implemented hardware efficiently suitable for the low resource utilization.